Quantum criticality in an organic spin-liquid insulator κ-(BEDT-TTF)2Cu2(CN)3 - Takayuki Isono (Nature Portfolio, 2016)
Quantum spin liquids emerge when quantum fluctuations suppress a magnetically ordered state. Here the authors measure magnetic torque inκ-(BEDT-TTF)2Cu2(CN)3, showing universal critical scaling in the magnetic susceptibilities, with critical exponents incompatible with known models for quantum spin liquids.